The Effect of Stick Dance Exercise to VO2 Max on ANC Semarang Gymnastic Studio Member - Cahyo, Andi Nur; Purnama, Yudhi (Indonesian Journal of Sport Management, 2024)
VO2 max is a critical indicator of cardiovascular fitness and aerobic capacity. Stick dance exercise is a low-impact, high-intensity activity that combines dance movements with resistance training. This study aimed to investigate the effect of stick dance exercise on VO2 max in ANC Semarang Gymnastic Studio members. Methods: This experimental study involved 30 randomly assigned participants to either a control group or an experimental group. The experimental group performed stick dance exercises for 12 times, while the control group did not participate in any exercise program. The results showed that the experimental group significantly increased VO2 max compared to the control group. The increase in VO2 max was 4,8% in the experimental group, indicating a substantial improvement in cardiovascular fitness. Stick dance exercises can effectively improve VO2 max in individuals new to exercise or with limited mobility.  Implications and The findings of this study have implications for the development of exercise programs that cater to diverse populations. Stick dance exercises can be valuable to existing exercise programs, particularly for individuals seeking low-impact, high-intensity activities.